Rabbits, Rabbits, Rabbits: Show Rabbit Record Book - Joy C. Jordan; Loretta Rodriguez; Jessica Kochert; Bill Heltemes; Chris Decubellis; Renee Gore (EDIS)
The 4-H Show Rabbit project focuses on all the aspects of showing rabbits according to the American Rabbit Breeders Association (ARBA) show guidelines, showmanship skills, and breed Standards of Perfection. Youth learn to asses a rabbit based on its Standard of Perfection, helping to identify faults and choose from reliable breeding stock. In the 4-H Show Rabbit project (visit http://florida4h.org for more information about this online project), youth learn the skills necessary for choosing a healthy rabbit, proper handling of a rabbit, rabbit health, and general care. This document, the Show Rabbit Record Book (4H RAR 12), familiarizes youth with the importance of record keeping as an integral part of project management. By tracking inventory, financial records associated with their project, rabbit health and grooming details, and related information such as monthly care schedules, show earnings, show registration/entry/remark cards, youth will be well prepared to relate their experiences in a written narrative as part of their project completion activities. First published September 2010.